Perancangan Identitas Visual Sarihon Ban untuk Memperkuat Kepercayaan Merek dan Daya Saing - Naka Nara Nata; Edy Chandra (Jurnal Desain Komunikasi Visual, 2026)
This study aims to design a new visual identity system for "Sarihon Ban," a local tire shop in Ciledug that has been operating since 2001, to strengthen brand trust and competitiveness amidst the dominance of modern automotive retail in the digital era. Despite having a strong historical reputation and customer loyalty, Sarihon Ban faces challenges in attracting new customers due to the lack of a professional and integrated visual identity. The research method employed is qualitative with a creative design approach, including data collection techniques such as field observation, documentation studies, and in-depth interviews with the business owner. Data were analyzed using Kapferer’s Brand Identity Prism framework to transform traditional values into a visual strategy relevant to the modern market. The design results established the concept of "Dynamic Professionalism," realized through an integrated wordmark logo. Key visual elements include a stylized letter ‘S’ forming an aerodynamic sports car silhouette, the letter ‘o’ representing a tire, the use of Speeday typography symbolizing speed, and a color palette of yellow and navy blue to create high visibility and a professional impression. This research concludes that consistent visual identity transformation across physical and digital media is a vital strategic intervention for traditional MSMEs to revitalize their brand image and ensure business sustainability in an increasingly competitive automotive market.